Crystalline Nitridophosphates by Ammonothermal Synthesis. Issue 9 (30th January 2020) - Mallmann, Mathias; Wendl, Sebastian; Schnick, Wolfgang
Abstract: Nitridophosphates are a well‐studied class of compounds with high structural diversity. However, their synthesis is quite challenging, particularly due to the limited thermal stability of starting materials like P3 N5 . Typically, it requires even high‐pressure techniques (e.g. multianvil) in most cases. Herein, we establish the ammonothermal method as a versatile synthetic tool to access nitridophosphates with different degrees of condensation. α‐Li10 P4 N10, β‐Li10 P4 N10, Li18 P6 N16, Ca2 PN3, SrP8 N14, and LiPN2 were synthesized in supercritical NH3 at temperatures and pressures up to 1070 K and 200 MPa employing ammonobasic conditions. The products were analyzed by powder X‐ray diffraction, energy dispersive X‐ray spectroscopy, and FTIR spectroscopy. Moreover, we established red phosphorus as a starting material for nitridophosphate synthesis instead of commonly used and not readily available precursors, such as P3 N5 . This opens a promising preparative access to the emerging compound class of nitridophosphates. Abstract : Nitridophosphates : Various nitridophosphates with different types of anionic PN4 tetrahedra‐based substructures were synthesized in supercritical ammonia using custom‐built high‐temperature, high‐pressure autoclaves. Red phosphorus was introduced as a starting material, emphasizing the innovative character of the ammonothermal approach (see figure).